O que brota das ruínas: o processo de ambientalização dos conflitos agrários em Alagoas - Lima, Weldja Marques da Silva (Universidade Federal de São Carlos, 2025)
This research examines the processes of environmentalization present in agrarian conflicts in Alagoas, with an emphasis on disputes between the sugar-alcohol sector and the Landless Rural Workers’ Movement (MST). The Zona da Mata region of Alagoas, characterized by the concentration of sugarcane monoculture and a significant number of land disputes, constitutes the main spatial focus of the investigation. The study seeks to understand how environmental issues have been appropriated and reinterpreted by these actors in the construction of their narratives and political strategies. Methodologically, the research adopts a qualitative approach, based on a literature review, secondary data analysis, quantitative and fieldwork. The specific objectives include: a) identifying and relating the historical formation of the sugarcane sector and the MST in Alagoas to environmental issues; b) analyzing the socio-environmental conflicts involving both groups; c) examining the discursive and marketing strategies employed by both the sugar-alcohol sector and the MST in the environmental debate; d) understanding the social and political motivations behind investments in agribusiness and social movements. By exploring these dynamics, the research contributes to the understanding of territorial and symbolic dispute mechanisms that shape contemporary agrarian conflicts, highlighting the role of environmental issues in the reconfiguration of these disputes. The phenomenon of the environmentalization of agrarian conflicts is understood as a dynamic and multifaceted process. This thesis contributes to the field by demonstrating how environmental issues have become a space of political dispute between antagonistic social classes. The main contribution lies in showing that environmentalization is not merely a discursive phenomenon but a mechanism for legitimizing different interests within the agrarian context. This process allows for an understanding of how class conflict is updated within the environmental agenda and how different actors appropriate this discourse to justify their actions.
Sprouting from the ruins: the process of evironmentalization of agrarian conflicts in Alagoas
Brotando de las ruinas: el proceso de ambientalización de los conflictos agrarios en Alagoas
Keywords: Conflitos agrários; Setor sucroalcooleiro; MST; Meio ambiente; Alagoas; Agrarian conflicts; Sugar-alcohol sector; Environment; Conflictos agrarios; Medio ambiente; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL